The Importance of Legal Framework in the Development of Halal Tourism in Indonesia - Dinda Bhawika Wimala Pastika; Amir Khoirudin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Muslim tourists may take advantage of a variety of Muslim-friendly tourism options, including halal tourism. A growing number of nations are considering expanding their halal tourist offerings, thanks to the industry's meteoric rise since 2018. Among 130 countries, Indonesia topped the 2019 Global Muslim Travel Index as the top halal tourist destination. This success has encouraged Indonesia to increase its efforts in developing halal tourism, taking use of the country's vast potential in this area. Indonesia's advantage in halal tourism must be complemented by particular legislation implementations governing halal tourism to enable structured and orderly implementation. With appropriate regulations, it is hoped that the optimization of halal tourism may become more structured in terms of standards in the promising halal tourism sector, acting as a benchmark for other nations to adopt halal tourism practices. This study aimed to provide additional information on the importance of adopting legislative standards for enforcing halal tourism legislation in Indonesia. This study used normative methodology. In addition to the need for special regulations concerning halal tourism management, careful preparation in terms of adequate scientific and technological updates is required to ensure that halal tourism in Indonesia is well received in the global market. Moreover, there must be a regular control in updating halal tourism regulations in Indonesia between authorized institutions